2013
DOI: 10.1186/1556-276x-8-282
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contact angle of water-based titanium oxide nanofluid

Abstract: This paper presents an investigation into spreading dynamics and dynamic contact angle of TiO2-deionized water nanofluids. Two mechanisms of energy dissipation, (1) contact line friction and (2) wedge film viscosity, govern the dynamics of contact line motion. The primary stage of spreading has the contact line friction as the dominant dissipative mechanism. At the secondary stage of spreading, the wedge film viscosity is the dominant dissipative mechanism. A theoretical model based on combination of molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…These are the manifestations of the interaction of the different molecular forces. The effects on the bulk thermo physical properties need to be addressed and surfactant dealt with nanofluids thus according to Radiom et al (2013). It was further found that NF+1OAK + decreased the water drop contact angle and surface tension to 38.23°and 28.69 mN/m, respectively (compared with pure water having 110°and 72.8 mN/m).…”
Section: The Contact Angle and Surface Tensionmentioning
confidence: 99%
“…These are the manifestations of the interaction of the different molecular forces. The effects on the bulk thermo physical properties need to be addressed and surfactant dealt with nanofluids thus according to Radiom et al (2013). It was further found that NF+1OAK + decreased the water drop contact angle and surface tension to 38.23°and 28.69 mN/m, respectively (compared with pure water having 110°and 72.8 mN/m).…”
Section: The Contact Angle and Surface Tensionmentioning
confidence: 99%
“…Energies 2019, 12,4558 Considering the origin is at the center of the wetting circle, r is the horizontal axis and z is the vertical axes of the droplet (Figure 1).…”
Section: Prediction Of Droplet Shapementioning
confidence: 99%
“…Estellé et al [10] have reviewed the surface tension and wettability and have concluded that nanoparticle nature, shape, size, content and concentration are governing parameters on surface tension and wettability. Some studies reported that the addition of nanoparticles increases the CA [11][12][13][14]. However, also a reduction in CA has also been observed in [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the contact line deformed around the defect but stayed intact away from it. Many experimental studies verified the enhanced pinning effect led by nanoparticles [37,[51][52][53][54][55]146]. In a study of microliter-sized droplets containing 250 nm gold particles, the droplet drying exhibited a second pinning stage rather than the behavior of a pure liquid droplet, revealing a significantly pronounced pinning effect [53].…”
Section: Effect Of Nanoparticles On Spreading Dynamicsmentioning
confidence: 99%
“…Nanoparticles sedimentation at the solid surface could vary the superficial structure and roughness of the wafer [36]. The roughened surface particularly in the vicinity of the contact line could lead to an inhomogeneity of the surface energy, and thus attract the contact line to a new site [36,37]. However, the droplet spreading at the initial stage is solely found in the nanofluid droplets instead of the pure water droplet, and behavior, and the pinning force, which were found to be dependent on the contact angle, the roughness and the heterogeneity of the solid surface [148].…”
Section: Mono-graphite Nanoparticle Concentrationmentioning
confidence: 99%